Progress in cryptology - INDOCRYPT 2015 : 16th International Conference on Cryptology in India, Bangalore, India, December 6-9, 2015 : proceedings /: 16th International Conference on Cryptology in India, Bangalore, India, December 6-9, 2015 : proceedings. (2015) - Unknown
No abstract available